PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI KERAGAMAN BUDAYA PULAU JAWA (KEBUJA) MAPEL PENDIDIKAN PANCASILA KELAS V SD - Hana Nur Khasanah; Wawan Priyanto; Ferina Agustini (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
This study aims to develop an app-based learning medium called KEBUJA, designed to enhance elementary school students’ engagement and understanding in Pancasila Education, particularly regarding the cultural diversity of Java. The background of this study is the limited availability of interactive learning media and the low level of student engagement in the learning process. Additionally, technological advancements and the widespread use of smartphones have exposed students to foreign cultures, leading to a lack of familiarity with their own local culture. The method used is research and development (R&D) employing the ADDIE model, which includes the analysis, design, development, implementation, and evaluation stages. The research subjects consisted of 1 teacher and 25 fifth-grade students at SD N Bawang 02. The research instruments included a subject matter expert validation sheet, a media expert validation sheet, and teacher and student response questionnaires. Data analysis techniques used percentages to determine the media’s validity and practicality. The results of the study indicate that the KEBUJA application features interactive elements such as visual materials, quizzes, and activities that encourage student participation. Validity testing revealed that the media falls into the “highly suitable” category, with a score of 97% from the media expert and 96% from the content expert. Additionally, the results of the practicality test showed a teacher response rate of 95% and a student response rate of 98.2%, which falls into the “highly practical” category. The use of ABSTRAK Penelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis aplikasi bernama KEBUJA yang dirancang untuk meningkatkan keaktifan dan pemahaman siswa sekolah dasar dalam pembelajaran Pendidikan Pancasila, khususnya pada materi keragaman budaya Pulau Jawa. Latar belakang penelitian ini adalah keterbatasan media pembelajaran yang interaktif serta rendahnya keterlibatan siswa dalam proses pembelajaran. Selain itu, perkembangan teknologi dan penggunaan smartphone menyebabkan siswa lebih terpapar budaya asing sehingga kurang mengenal budaya daerahnya sendiri. Metode yang digunakan adalah penelitian dan pengembangan (Research and Development/R&D) dengan model ADDIE yang meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Subjek penelitian terdiri dari 1 orang guru dan 25 siswa kelas V SD N Bawang 02. Instrumen penelitian meliputi lembar validasi ahli materi, lembar validasi ahli media, serta angket respon guru dan siswa. Teknik analisis data menggunakan persentase untuk menentukan tingkat kevalidan dan kepraktisan media. Hasil penelitian menunjukkan bahwa aplikasi KEBUJA memiliki fitur interaktif berupa materi visual, kuis, dan aktivitas yang mendorong partisipasi siswa. Uji validitas menunjukkan bahwa media berada pada kategori sangat layak dengan skor 97% dari ahli media dan 96% dari ahli materi. Selain itu, hasil uji kepraktisan menunjukkan respon guru sebesar 95% dan respon siswa sebesar 98,2%, yang termasuk kategori sangat praktis. Penggunaan aplikasi Kebuja juga menunjukkan peningkatan keaktifan dan pemahaman siswa selama pembelajaran.